ALTERNATIF RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK KEKERASAN DALAM RUMAH TANGGA - M. Rudi Hartono (Universitas Batanghari Jambi, 2014)
In the household, tensions and conflicts are a common thing. Disagreement, debate, arguments, teasing or even yelling at each other is a common thing to happen. But all that may be part of a form of domestic violence which specifically refers to the definition of violence against women.Justice will come true when using a process that is the law of justice, through a board that is justice, the judicial process by the law of reciprocity is an integral, the law requires judicial process to establish fairness and justice but also would require law because justice without law will not adhered to by the community.However, the domestic violence case not closed the possibility of settlement of a dispute or a case of domestic violence outside the formal court process, or better known as restorative justice. Restorative justice itself aims wherever possible to reduce the consequences caused by criminal behavior, attention and handling of this concept involves all affected parties, including the actors themselves.Keyword : Crime, Law, justice